Acute and sub-acute sinus node dysfunction following pulmonary vein isolation: a case series. Issue 1 (5th January 2018) - Barra, Sérgio; Gopalan, Deepa; Baran, Jakub; Fynn, Simon; Heck, Patrick; Agarwal, Sharad
Abstract: Six patients submitted to paroxysmal atrial fibrillation (AF) ablation presented with long post-reversion sinus pauses between a few hours to 2 months after their procedures, causing recurrent syncope or pre-syncope. Five patients required urgent pacemaker implantation. None of these patients had previous symptoms suggestive of sick sinus syndrome (SSS) or a history of symptomatic bradycardia. Acute or sub-acute sinus node dysfunction (SND) has only recently been suggested as a potential complication of AF ablation. In three of our patients, the sinus node artery (SNA) was exclusively left-sided, running along the high anterior left atrium in close proximity to the ostia of the left and right superior pulmonary veins. In a fourth case, the SNA originated from the right coronary artery and coursed along the high anterior left atrium close to the ostium of the right superior pulmonary vein. In the remaining two cases, a pre-procedural assessment of the SNA was not possible, although a post-procedural CT scan performed in one of these did not reveal any signs of the SNA. Overdrive suppression of the sinus node exacerbated by thermal injury to the SNA may have been implicated. This was supported by (i) the lack of symptoms/signs suggestive of SSS pre-ablation, (ii) post-ablation acute/sub-acute pronounced post-AF reversion sinus pauses, and (iii) the observation that the SNA coursed along areas typically ablated during an AF ablation. Although this case series is hypothesis-generating only, we hope it will raise the awareness for the occurrence of acute/sub-acute SND as a potential complication of AF ablation.